2012
DOI: 10.1111/j.1365-2702.2012.04090.x
|View full text |Cite
|
Sign up to set email alerts
|

Surviving, not thriving: a qualitative study of newly qualified midwives’ experience of their transition to practice

Abstract: Whilst further work is required, the findings provide a deeper understanding of individual midwives' transition period. The importance of forming longitudinal relationships not only with women but with midwifery colleagues is highlighted. Developing continuity models that adequately support graduates and student's needs are likely to assist in addressing practices issues in both the academic and clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 30 publications
(49 reference statements)
4
77
0
Order By: Relevance
“…Continuity of care experiences can also facilitate a smooth transition to practice. Fenwick et al (2012) interviewed 16 new midwifery graduates and found that continuity with women enhanced confidence and restored faith in normal birth. This confidence is important as the midwifery culture of some institutions remains highly contested with midwives struggling to provide woman-centred care and are often challenged by the risk-averse nature of maternity care.…”
Section: Discussionmentioning
confidence: 98%
“…Continuity of care experiences can also facilitate a smooth transition to practice. Fenwick et al (2012) interviewed 16 new midwifery graduates and found that continuity with women enhanced confidence and restored faith in normal birth. This confidence is important as the midwifery culture of some institutions remains highly contested with midwives struggling to provide woman-centred care and are often challenged by the risk-averse nature of maternity care.…”
Section: Discussionmentioning
confidence: 98%
“…Evidence suggests that many new graduates want and expect to work across their full scope of practice in a continuity of midwifery care model (Carter, Wilkes, Gamble, Sidebotham, & Creedy, ; Dawson, Newton, Forster, & McLachlan, ; Hammond, Gray, Smith, Fenwick, & Homer, ). However, newly qualified midwives may find a workplace that is hierarchical in nature, medically dominated, lacking a woman‐centred approach to care and providing limited opportunity to access models of continuity of care (Fenwick et al., ; Hunter, ). These are all potential reasons why work‐related burnout was highest in this group of midwives.…”
Section: Discussionmentioning
confidence: 99%
“…Such experiences further solidified the nursing identity and nursing spirit, and also provided positive anticipation and active participative attitudes for follow-on practices. Therefore, in order to facilitate nursing students to undergo a successful transition, clinical practices that are strongly related to theories need to be provided [4] , receiving respect and support from professors or clinical instructors is needed [16] , and positive relationships among colleagues would need to be strengthened [17] . Additionally, for nursing students to raise their senses of salience, cooperation and responsibility as well in clinical practice, rather than staying in the observation stage, it would be important to increase actual practice experience under the supervision of nurses or clinical instructors [8] .…”
Section: Discussionmentioning
confidence: 99%